'˜TEST-NEGATIVE ANGELMAN SYNDROME' WITH THYROID DYSFUNCTION: A RARITY BUT A REALITY! - Ali, Mohammad Usman; Mehmood, Anjum; Ali, Mahrukh Ayesha (Journal of Ayub Medical College Abbottabad, 2015)
Angelman Syndrome (AS) is believed to be a complex neuro-developmental genetic disorder that is often described clinically by the presence of behavioural uniqueness and movement disorders; in addition to having developmental delay and speech impairment. Genetic factors have been linked to the syndrome's aetiology in 90% of cases, although in 10% cases, an unidentified genetic mechanism accounts for the classic phenotypic features of AS. Angelman Syndrome in general or with associated thyroid dysfunction, have never been reported from Pakistan. This is the first ever case report from Pakistan reporting a rare case of clinically diagnosed AS with associated thyroid dysfunction in the presence of normal molecular genetic testing (DNA methylation test and UBE3A gene sequencing). In future, clinicians should make efforts in documenting similar cases with associated clinical profiles from our part of the world, thereby contributing to the local and regional epidemiology of these syndromes.